Analisis Instagram Ads Sebagai Media Promosi Jasa Dalam Meningkatkan Brand Awareness Pada Exsis Barbershop Di Tangerang Selatan - Shalshabilla Balkisty; Alikarahma Nur Falah; Dwi Helen Aprilizah; Irvan Firmansyah; Larasati Ahmad Suyono; Widya Septiyani; Derizka Inva Jaswita (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to find out about Instagram ads as a service promotion media in increasing brand awareness at Exsis Barbershop. The research method used is a type of qualitative research using SWOT analysis techniques, participatory observation and direct interviews with The Key Informants, namely the owner of Exsis Barbershop, and Focus Group Discussion (FGD) with several employees and barbershop customers. The results of qualitative research show that there is a shift in promoting a brand in the barbershop service industry through Instagram ads which has created a drastic trend for customers to view and use barbershop services Keywords: Instagram ads, Brand Awareness, Barbershop